2003
DOI: 10.1093/aje/kwg139
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Increased and Decreased Risk of Campylobacter Infection: A Prospective Case-Control Study in Norway

Abstract: In 1999-2000, a prospective case-control study of sporadic, domestically acquired campylobacteriosis was conducted in three counties in Norway to identify preventable risk factors and potentially protective factors. A total of 212 cases and 422 population controls matched by age, sex, and geographic area were enrolled. In conditional logistic regression analysis, the following factors were found to be independently associated with an increased risk of Campylobacter infection: drinking undisinfected water, eati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
201
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(222 citation statements)
references
References 31 publications
11
201
2
4
Order By: Relevance
“…Such 'protective ' effects have been observed in many previous casecontrol studies [13,15,18]. Frequently mentioned explanations are differences in food preferences or immune status between cases and controls, statistical coincidences or bias.…”
Section: Y Doorduyn and Othersmentioning
confidence: 66%
See 2 more Smart Citations
“…Such 'protective ' effects have been observed in many previous casecontrol studies [13,15,18]. Frequently mentioned explanations are differences in food preferences or immune status between cases and controls, statistical coincidences or bias.…”
Section: Y Doorduyn and Othersmentioning
confidence: 66%
“…0) 14 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) Contact with persons with gastroenteritis symptoms outside the household (20) 21 (20) 38 (8) 2 . 8 (1 .…”
Section: -5mentioning
confidence: 99%
See 1 more Smart Citation
“…Case-control studies of food borne infection rates have estimated that 50-70% of Campylobacter illness is due to consumption of contaminated poultry and their products (Tauxe et al, 1985;Allos, 2001;Kapperud et al, 2003). Several studies examined thermophilic Campylobacter in poultry and the findings indicated prevalence ranges of the Campylobacter from 3-98% with C. jejuni as the main isolates (Kapperud et al, 2003;Cardinale et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Case-control studies of potential risk factors for campylobacteriosis have been undertaken in several countries [4][5][6][7][8][9][10][11] including Australia [12,13]. Consumption of chicken is the most commonly identified risk factor for sporadic campylobacteriosis.…”
Section: Introductionmentioning
confidence: 99%